An overview of basic econometrics: a short notes e-book / Nur Fadhlina Zainal Abedin and Faridah Pardi - Zainal Abedin, Nur Fadhlina; Pardi, Faridah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The eBook 'Basic Econometrics: An Overview' represents a significant teaching and learning innovation in the field of economics education. This resource simplifies the traditionally complex subject of econometrics, making it more accessible to students. Through a blend of clear explanations, engaging visuals, and an overview-oriented approach, the eBook empowers learners to grasp fundamental econometric concepts with ease. Moreover, it not only prepares students for advanced textbooks but also offers a vision of future commercialization with additional content, exercises, and game-based learning elements. This eBook not only enhances the understanding of econometrics but also aligns with environmental sustainability by promoting digital educational resources. It marks a promising step towards a more student-friendly, interactive, and environmentally conscious approach to teaching and learning.